Entrepreneurial Exits and Innovation - Aggarwal, Vikas A.; Hsu, David H. (Management Science, 2014)
We examine how initial public offerings (IPOs) and acquisitions affect entrepreneurial innovation as measured by patent counts and forward patent citations. We construct a firm-year panel data set of all venture capital-backed biotechnology firms founded between 1980 and 2000, tracked yearly through 2006. We address the possibility of unobserved self-selection into exit mode by using coarsened exact matching, and in two additional ways: (1) comparing firms that filed for an IPO (or announced a merger) with those not completing the transaction for reasons unrelated to innovation, and (2) using an instrumental variables approach. We find that innovation quality is highest under private ownership and lowest under public ownership, with acquisition intermediate between the two. Together with a set of within-exit mode analyses, these results are consistent with the proposition that information confidentiality mechanisms shape innovation outcomes. The results are not explained by inventor-level turnover following exit events or by firms' preexit window dressing behavior. This paper was accepted by Lee Fleming, entrepreneurship and innovation.